2021
DOI: 10.1159/000513777
|View full text |Cite
|
Sign up to set email alerts
|

Study Design and Baseline Characteristics of the CARDINAL Trial: A Phase 3 Study of Bardoxolone Methyl in Patients with Alport Syndrome

Abstract: <b><i>Introduction:</i></b> Alport syndrome is a rare genetic disorder that affects as many as 60,000 persons in the USA and a total of 103,000 persons (&#x3c;5 per 10,000) in the European Union [1, 2]. It is the second most common inherited cause of kidney failure and is characterized by progressive loss of kidney function that often leads to end-stage kidney disease. Currently, there are no approved disease-specific agents for therapeutic use. We designed a phase 3 study (CARDINAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
1
31
0
6
Order By: Relevance
“…2,59,120,121 As patients with Alport syndrome experience a loss of kidney function despite the use of angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers and there is a documented inflammatory component, the effects of Nrf2 stimulation with bardoxolone methyl are currently investigated in a randomized controlled trial (CARDINAL). 122…”
Section: Alport Syndromementioning
confidence: 99%
“…2,59,120,121 As patients with Alport syndrome experience a loss of kidney function despite the use of angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers and there is a documented inflammatory component, the effects of Nrf2 stimulation with bardoxolone methyl are currently investigated in a randomized controlled trial (CARDINAL). 122…”
Section: Alport Syndromementioning
confidence: 99%
“…Thus far, this type of therapeutic approach is to be considered the most effective, pending the results of the most recent studies on more modern therapies. In fact, more recently, studies have focused on new therapeutic options such as Bardoxolone [ 21 ], anti-microRNA-21 [ 22 ], stem cell-based therapies [ 23 ]. Furthermore, a recent innovation is the so-called “exon skipping therapy”, which, in mice with reduced expression of the α5 (IV) chain, has led to remarkable clinical and pathological improvements, including a higher expression of the α5 chain on glomerular and the tubular basement membrane, with better survival [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bardoxolone is an inducer of the Nuclear factor erythroid 2-related factor 2 (NRF2) and was a promising therapeutical agent [ 50 ]. Different clinical trials reported that patients diagnosed with diabetic nephropathy, late stage CKD [ 51 ], glomerulosclerosis and polycystic kidney disease had a significant recovery in GFR when treated with bardoxolone [ 52 ]. NRF2 is a transcription factor central to several regulatory mechanisms in mice models in which this factor is dysregulated or knocked-out; the animals developed glomerular damage and fibrosis leading to the loss of renal function [ 53 ].…”
Section: Prospective New Therapies For Ckdmentioning
confidence: 99%